2011
DOI: 10.1007/s00232-011-9383-5
|View full text |Cite
|
Sign up to set email alerts
|

K+ Channels of Squid Giant Axons Open by an Osmotic Stress in Hypertonic Solutions Containing Nonelectrolytes

Abstract: In hypertonic solutions made by adding nonelectrolytes, K(+) channels of squid giant axons opened at usual asymmetrical K(+) concentrations in two different time courses; an initial instantaneous activation (I (IN)) and a sigmoidal activation typical of a delayed rectifier K(+) channel (I (D)). The current-voltage relation curve for I (IN) was fitted well with Goldman equation described with a periaxonal K(+) concentration at the membrane potential above -10 mV. Using the activation-voltage curve obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In the preceding section, there was no restriction on the solute size, and the KB theory can now be applied to systems much larger than those studied before, such as ion channels and actin polymerization. , …”
Section: The “Osmotic Pressure” Vs the Hydrostatic Pressurementioning
confidence: 99%
See 3 more Smart Citations
“…In the preceding section, there was no restriction on the solute size, and the KB theory can now be applied to systems much larger than those studied before, such as ion channels and actin polymerization. , …”
Section: The “Osmotic Pressure” Vs the Hydrostatic Pressurementioning
confidence: 99%
“…The answer for the adsorption theory is the Gibbs dividing surface. ,,,, By appropriately positioning the dividing surface, the surface excess of water can be made zero. ,,,, The surface-tension change due to the introduction of the cosolvents can therefore be attributed entirely to the surface excess of the cosolvent. ,, The indeterminate problem can thus be circumvented elegantly by introducing the dividing surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature change impacts the function of the nervous system by affecting synaptic gain, as well as synaptic and conduction delays [17]. In their pioneering study of the electrical activity of the squid giant axon, Hodgkin and Katz found that the falling phase of the action potential was particularly sensitive to temperature [18], which was later shown to be caused by the temperature sensitivity of the gating property and closing kinetics of the potassium channel [19]. In cold temperatures, in the absence of functional adjustment through RNA editing, the delayed closing of the potassium channel would broaden the action potential, thereby limiting the firing frequency [20].…”
Section: Introductionmentioning
confidence: 99%